Development and Management of Islamic Education Curriculum In The Covid-19 Pandemic: Case Study at SMP IT Mutiara Kab. Deli Serdang North Sumatra - Aktar, Salim; Amini, Amini; Pratiwi, Sri Nurabdiah (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to describe curriculum development during the Covid-19 pandemic at SMP IT Mutiara, Deli Serdang Regency, North Sumatra. A qualitative approach is used in this study with the case study method. In an effort to reveal the facts and phenomena surrounding the curriculum development, the researchers collected data through interviews, observation, and documentation studies. Furthermore, the data were analyzed using data reduction techniques, data presentation, and drawing conclusions. The results of this study concluded that the development of the IT Mutiara Middle School learning curriculum during the Covid-19 pandemic was managed effectively, also taking into account the principles of safety and security for school residents according to applicable regulations. This is marked by 5 aspects, namely (1) the planning aspect, including meetings with the management and teachers of SMP IT Mutiara, consultation with the school's managerial supervisor, and approval of the plan from the Deli Serdang education office, (2) organizational aspects, including the curricular with an eye group A and B lessons, co-curricular, extra-curricular with scouts and tahfiz of the Qur'an, as well as local content on information and communication technology (ICT) material, (3) implementation aspects, five days (Monday-Friday) effective learning days , Saturdays extracurricular activities with the person in charge of the teachers who have been determined, (4) aspects of supervision, including direct supervision by the school principal and school managerial supervisors, related to academic administration and services, and (5) evaluation aspects including a review of the achievement of goals and process of the learning system, so that curriculum implementation can be analyzed, making accountability reports, and recommendations for next steps.